International Trade Statistics Yearbook 2013, Volume I - United Nations Department of Economic; Social Affairs (United Nations, 2015)
The 2013 International Trade Statistics Yearbook, Volume I provides an overview of the international trade merchandise trade in 2013 and detailed information on the trade performance for numerous countries up to 2013. Overall, data for a total of 175 countries (or areas) are shown with the 2013 data on imports and exports by commodity and trading partner provided for approximately 90 countries (or areas), representing more than 70% of world trade of 2013. The goal is to provide a more analytical and condensed view of trade by using graphs, overview tables and descriptive text.